Protein Profiling of Arabidopsis Roots Treated With Humic Substances: Insights Into the Metabolic and Interactome Networks - Roomi, Sohaib; Masi, Antonio; Conselvan, Giovanni Battista; Trevisan, Sara; Quaggiotti, Silvia; Pivato, Micaela; Arrigoni, Giorgio; Yasmin, Tayyaba; Carletti, Paolo (Frontiers in Plant Science, 2018)
Background and aim Humic substances (HS) influence the chemical and physical properties of the soil, and are also known to affect plant physiology and nutrient uptake. This study aimed to elucidate plant metabolic pathways and physiological processes influenced by HS activity. Methods Arabidopsis roots were treated with HS for eight hours. Quantitative mass spectrometry-based proteomics analysis of root proteins was performed using the iTRAQ (Isobaric Tag for Relative and Absolute Quantification) technique. Out of 902 protein families identified and quantified for HS treated vs untreated roots, 92 proteins were differentially expressed. Bioinformatic tools such as STRING, KEGG, IIS and Cytoscape were used to interpret the biological function, pathway analysis and visualization of network amongst the identified proteins. Results From this analysis it was possible to evaluate that most of the differentially expressed proteins were functionally classified into several categories, mainly redox homeostasis, response to inorganic substances, energy metabolism, protein synthesis, cell trafficking and division. Conclusions In the present study an overview of the metabolic pathways most modified by HS biological activity is provided. Moreover, from the analysis of interactomes it was possible to observe previously undiscovered, novel HS effects, i.e. on the Ubiquitin subnetwork.